Strategi Optimalisasi Pengelolaan Wakaf Tanah: Analisis Bibliometrik - Muhamad Arul Rizky; Indra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the optimization strategy of land waqf management using a bibliometric approach conducted using biblioshiny, an R-based application. Descriptive statistical methods were used, Data were analyzed from 189 research publications in scopus with the keyword